Pengaruh Karakteristik Individu Dan Karakteristik Pekerjaan Terhadap Komitmen Organisasi Pegawai Di PT Gokko Mirai Indonesia Tahun 2023 - Yahya, Muhamad Firly; Bagus, Wanta; Romli, Asep Darojatul (Jurnal Ilmiah Wahana Pendidikan, 2024)
One aspect that can influence organizational commitment is individual characteristics and job characteristics. Individual characteristics are a psychological process that influences individuals in obtaining, consuming and receiving goods and services and experiences. Individual characteristics are internal factors that drive and influence individual behavior so that they have different abilities from other people to maintain and improve work within the organization. The type method in this study uses a type of qualitative research, which places more emphasis on descriptive analysis and discussion. Qualitative methods will focus more on incidents in the research environment, which are more focused on elements or groups of people, objects, institutions, relationships with elements and receiving data appropriately. Individual characteristics and job characteristics influence the search for new employees, companies adjust certain jobs filled by who and how good the employee is, individual characteristics and job characteristics influence because we know what abilities and jobs are given and to develop potential as well. Individual characteristics and job characteristics are influential because according to the test mechanism that matches these characteristics, various tests are carried out to determine accuracy, intelligence, skill, because in each test there is a score to be accepted or not so it is very influential. Individual characteristics and job characteristics affect organizational commitment because they will be placed in the appropriate position and the parts needed by the company. The existence of the influence of employee organizational commitment to the company with the existence of individual characteristics and the characteristics of the company's work will make it easier to place employees. The employee's trust in the company is further enhanced, and has good attitude and discipline, both within the company and outside the company.